2022
DOI: 10.1002/jsfa.11793
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic composition, antioxidant and antiacetylcholinesterase activities of Opuntia ficus‐indica peel and flower teas after in vitro gastrointestinal digestion

Abstract: BACKGROUND The flowers and peels of cactus Opuntia ficus‐indica (OFI) are by‐products generally discarded. Their beneficial properties have been linked to the chemical composition without taking into account its transformations during digestion. This study evaluated and compared the phenolic composition, antioxidant and antiacetylcholinesterase activities of OFI peel and flower teas before and after in vitro gastrointestinal digestion. RESULTS Results showed that OFI peel tea was a source of natural phenolic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 44 publications
(116 reference statements)
1
13
1
Order By: Relevance
“…Moreover, many studies have reported the presence of phenolic acids, such as coumaric acid, quinic acid, piscidic acid, eucomic acid, and other compounds in fruit, pulp, and peel OFI extracts [ 17 , 31 , 41 , 42 ]. Also, Amrane-Abider et al [ 10 ] identified some phenol compounds, namely quercetin-3-O-rutinoside, isorhamnetin, isoquercetin, and kaempferol-3-O-rutinoside in Opuntia ficus-indica peel and flower teas using the boiling water method. These differences may be due to genetic factors, prickly pear varieties, culture or growth conditions, and geographical variations in prickly pear plants [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, many studies have reported the presence of phenolic acids, such as coumaric acid, quinic acid, piscidic acid, eucomic acid, and other compounds in fruit, pulp, and peel OFI extracts [ 17 , 31 , 41 , 42 ]. Also, Amrane-Abider et al [ 10 ] identified some phenol compounds, namely quercetin-3-O-rutinoside, isorhamnetin, isoquercetin, and kaempferol-3-O-rutinoside in Opuntia ficus-indica peel and flower teas using the boiling water method. These differences may be due to genetic factors, prickly pear varieties, culture or growth conditions, and geographical variations in prickly pear plants [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Opuntia flowers have long been used in folk medicine for a wide variety of therapeutic effects against ocular illnesses [ 6 ], diabetes [ 7 ], ulcers [ 8 ], and renal lithiases [ 9 ]. Moreover, the organic extracts of OFI flowers were studied for their antiacetylcholinesterase [ 10 ] and anti-inflammatory effects [ 11 ]. Furthermore, some Opuntia species showed inhibitory activity against P. aeruginosa , S. aureus , and E. coli , and others could be used as food preservative agents [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These extracellular enzymes act on phenolic components, and from a chemical point of view, glycosylation, methylation and other types of substitutions are carried out, resulting in structural changes. This lead to the mutual conversion of phenolic substances in the sample, thereby changing their oxidative activity ( 45 ). The p-hydroxybenzoic acid content decreased by approximately 17.95% after fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…This economic model is based on rules and principles of sustainable development, including respect for the environment by limiting waste and recovering by-products [1][2][3]. Opuntia ficus-indica peels (OFI) are one of the most important by-products generated by the prickly pear cactus industry; their percentage can exceed 40% up to 55% of the whole weight of the fruit [4,5]. OFI peels are rich in proteins, vitamins, minerals, and carbohydrates (dietary fiber and pectin) as well as bioactive substances known for their source of beneficial properties.…”
Section: Introductionmentioning
confidence: 99%